Guidance on patient Identification and Administration of Recombinant Human Activated protein C for the Treatment of Severe Sepsis. (1st December 2002) - Garber, Gary; Gibney, RT Noel; Light, Bruce; Martin, Claudio; Cunningham, Kenneth; Guimond, Jean-Gilles; Magder, Sheldon; Russell, James
Abstract : Approximately one-third of cases of severe sepsis result in death. Endogenous activated protein C (ApC) plays a key role in the regulation of the inflammation, fibrinolysis and coagulation associated with severe sepsis. In a recently published phase III trial, protein C Worldwide Evaluation in Severe Sepsis (pROWESS), intravenous administration of recombinant human ApC (rhApC) 24 µg/kg/h for 96 h to patients with severe sepsis resulted in a 6.1% reduction in absolute mortality and a 19.4% reduction in the relative risk of death from any cause within 28 days (number needed to treat = 16). This dose is now being applied in clinical practice. rhApC is recommended for the treatment of severe sepsis (sepsis associated with acute organ dysfunction) occurring as a result of all types of infection (Gram-negative bacterial, Gram-positive bacterial and fungal). A panel of Canadian clinicians experienced in the treatment of severe sepsis and the management of critical care patients has developed this consensus document to assist clinicians in appropriate patient selection and management of potential challenges associated with rhApC therapy.